Comparison of the antioxidant effect of Vitamin C and Garlic extract in hyperglycemic cataractous goat lenses: An experimental study - Hajarnavis, Dr. Arti M; More, Dr. Umesh K; Bulakh, Dr P M (South Eastern European Journal of Public Health, 2025)
Background: Cataract remains the leading cause of blindness worldwide, while diabetes mellitus intensifies the development of cataracts. Hyperglycemia triggers oxidative stress that produces ROS, which causes protein aggregation and lipid peroxidation. Garlic Extract (Allium sativum) and Vitamin C present therapeutic potential in the combat of oxidative stress for preventing lens opacification. Methods: In this study, 30 goat lenses were incubated with TC199 for 72 hours to serve as a control. The experimental group consisted of 3 groups of 30 Goat lenses, each incubated with dextrose, garlic water extract + dextrose, and vitamin C + dextrose, respectively. A study was made on the changes in lens morphology, total soluble proteins MDA level, and activity of Superoxide Dismutase, Glutathione Peroxidase, and Glutathione Reductase. Results: The dextrose-induced cataract lenses experienced a 25.8% decrease in total soluble proteins and a 28.9% increase in MDA levels, and a significantly lowered activity of SOD, GPx, and GRx as compared to control, indicating that severe oxidative damage occurred. Protein content was preserved in lenses treated with Garlic Extract and Vitamin C in a significant way. At the same time, MDA levels decreased, and activities of all antioxidant enzymes increased in lenses treated with Garlic Extract and Vitamin C. Conclusion: The experimental findings show that both Garlic Extract and Vitamin C successfully minimize oxidative stress while improving lens transparency in diabetic cataract conditions. Garlic Extract demonstrates better performance than Vitamin C by restoring enzymes and exhibiting stronger antioxidant properties, and thus, it could serve as a natural anti-cataractous agent.